Structural and Morphological Characterization of MEH-PPV/Ag Composite - Suha Ahmad Jawad; Mustafa Mohammed Ali Hussein (Iraqi Journal of Physics, 2024)
In this study, spin coating was used to prepare thin films of poly (2-methoxy-5-(2-ethylhexyloxy)-1, 4-phenylene vinylene) and silver (MEH-PPV/Ag) in this study. The physical characteristics of MEH-PPV/Ag thin films with various weight ratios (0.01, 0.02, 0.03, and 0.04%) were investigated by Fourier-transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FE-SEM), atomic force microscopy (AFM), X-ray diffraction analysis (XRD), and thermal testing. FTIR analysis showed that there were occurrences of the polymer's predicted chemical bonds. AFM tests show that when different amounts of silver are added to a polymer matrix, the film's surface roughness (root mean square) goes up from an average of 83.51 to 511.3 nm. FE-SEM analysis showed that a pure sample of the polymer formed evenly. However, when different amounts of Ag were added, clear balls or circles formed, showing the energy of mixing between the MEH-PPV and Ag. As silver addition transformed the polymer from amorphous to polycrystalline, XRD analysis revealed both phases. In tests comparing pure MEH-PPV to MEH-PPV/Ag, the polymer containing silver showed higher thermal conductivity.